2017
DOI: 10.1177/2055217317727296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D3 in clinically isolated syndrome and healthy control participants: A double-blind randomised controlled trial

Abstract: BackgroundLowserum vitamin D levels are associated with susceptibility to, and severity of, multiple sclerosis. High dose vitamin D has been proposed as a potential immunomodulator in multiple sclerosis.ObjectivesWe performed a single centre, investigator-led, exploratory, double-blind, randomised, placebo controlled, trial of vitamin D3 in clinically isolated syndrome and healthy control participants to assess its immunological effects. Secondary end-points included clinical and magnetic resonance imaging out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…While the above studies reported encouraging results, four studies in this review showed results that were not as positive (O'Connell et al, 2017;Holmoy et al, 2017;Muris et al, 2016b;Rosjo et al, 20115). Holmoy et al (2017) and Rosjo et al (2015) examined bone health in RRMS patients who received 20,000 IU D3 weekly over 96 weeks.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…While the above studies reported encouraging results, four studies in this review showed results that were not as positive (O'Connell et al, 2017;Holmoy et al, 2017;Muris et al, 2016b;Rosjo et al, 20115). Holmoy et al (2017) and Rosjo et al (2015) examined bone health in RRMS patients who received 20,000 IU D3 weekly over 96 weeks.…”
Section: Discussionmentioning
confidence: 65%
“…Rosjo's group, however, did see the serum 25(OH)D levels more than doubled for the group receiving the supplements. O'Connell et al (2017) noted no difference in pro-inflammatory CD4+ T cells and while they observed a higher level of disease freedom, it was not at a significant level. This group admitted that further study is needed in this area.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…No significant differences were observed in the concentrations of IL-10, IL-17 and IFN-gamma produced followed stimulation of peripheral blood mononuclear cells (PBMCs) in any treatment arm. Moreover, no significant reduction in the frequency of proinflammatory CD4 T cells was seen [34]. Only Ashtari et al showed that in RRMS patients IL-10 serum level increased significantly after taking high-dose vitamin D3 for three months [35].…”
Section: Cd4+ T Cellsmentioning
confidence: 98%